Collective memory and coloniality of being as a hermeneutical framework : a partialised reading of Ezra-Nehemiah - Snyman, Gerrie 19XX- (Old Testament essays, 2007)
The essay pleads for letting the memory of apartheid be part of the hermeneutical framework in reading the Bible. To argue the case, the author illustrates the dilemma with a problematic reading and sermon within the RCSA of the strange or foreign women in Ezra 9-10. There is a need to develop a hermeneutic that will enable those who are associated with a perpetrator disgraced culture to reconstruct themselves. A hermeneutic that fails to take seriously the effects of reading would be powerless to address the concerns of those dealing with the bad memories of the past and the construction of a new identity. To address his concerns and to support his appeal, the author intends looking at the following : the role of memory, coloniality of being and whiteness within a perpetrator culture, a theology of reconstruction and another understanding of the strange women in Ezra 9-10.